Racial harassment, ethnic concentration and economic conditions - Christian Dustmann; Francesca Fabbri; Ian Preston (Institute for the Study of Labor (IZA), 2010)
In this paper, we analyse the association between spatial concentration of ethnic minorities, and racial harassment. Ethnic concentration relates to racial harassment through at least three channels: hostility in attitudes of majority individuals that find expression in harassment behaviour, the probability of minority individuals meeting majority individuals, and the cost of expressing hostility aggressively. Harassment can thus not simply be modeled as a stronger form of hostility. Using unique data for Britain, we show that, in area of higher local ethnic concentration, experience of harassment is lower, even though hostility on the side of the majority population is not.
Keywords: J15; R23; 330; Economics of minorities; interracial relations; Ethnische Diskriminierung; Ethnische Beziehungen; Ethnische Gruppe; Segregation; Regionale Konzentration; Großbritannien